Enhanced exudation of malate in the rhizosphere due to AtALMT1 overexpression in blackgram (Vignamungo L.) confers increased aluminium tolerance. (29th April 2020) - Saha, B.; Swain, D.; Borgohain, P.; Rout, G. R.; Koyama, H.; Panda, S. K.
Abstract: Worldwide, 50% of soil is acidic, which induces aluminium (Al) toxicity in plants, as the phyto‐availability of Al 3+ increases in acidic soil. Plants responds to Al 3+ toxicity by exuding organic acids into the rhizosphere. The organic acid responsible for Al 3+ stress response varies from species to species, which in the case of blackgram ( Vigna mungo L.) is citrate. In blackgram, an Arabidopsis malate transporter, At ALMT1, was overexpressed with the motive of inducing enhanced exudation of malate. Transgenics were generated using cotyledon node explants through Agrobacterium tumefaciens ‐mediated transformation. The putative transgenics were initially screened by At ALMT1‐specific genomic DNA PCR, followed by quantitative PCR. Two independent transgenic events were identified and functionally characterized in the T3 generation. The transgenic lines, Line 1 and 2, showed better root growth, relative water content and chlorophyll content under Al 3+ stress. Both lines also accounted for less oxidative damage, due to reduced accumulation of ROS molecules. Photosynthetic efficiency, as measured in terms of Fv /Fm, NPQ and Y(II), increased when compared to the wild type (WT). Relative expression of genes ( Vm STOP1, Vm ALS3, Vm MATE) responsible for Al 3+ stress response in blackgram showed that overexpression of a malate transporter did not have any effect on their expression. Malate exudation increased whereas citrate exudation did not show any divergence from the WT. A pot stress assay found that the transgenics showed better adaptation to acidic soil. This report demonstrates that the overexpression of a malate transporter in a non‐malate exuding species improves adaptation to Al 3+ toxicity in acidic soil without effecting its stress response mechanism. Abstract : Blackgram ( Vigna mungo L.), a citrate (in excess) exuding species in response to aluminium toxicity in acidic soil, was transformed with At ALMT1 (a malate transporter), resulting in increased malate exudation in the rhizosphere which in turn enhanced tolerance without effecting the citrate exudation pathway.